Cardiac and Inflammatory Biomarker Signatures in Hyperthyroidism Treated with 35 mg Carbimazole: Influence of Pre-Existing Heart Disease - Nawar fadhil Razooqi (American Journal of Biomedicine and Pharmacy, 2026)
Background: Hyperthyroidism changes cardiovascular, inflammatory, and metabolic pathways. These changes may be aggravated by heart disease. Objective: Both to compare levels of thyroid hormones, proBNP, IL-6, lipid profile, renal function, glucose, and BMI among four groups and to determine whether or not proBNP and IL-6 can detect cardiac disease in hyperthyroid patients. Methods: It was an analytical cross-sectional study, which utilized a dataset of 140 participants (n = 50 healthy controls, n = 30 hyperthyroidism treated with 35 mg carbimazole, n = 30 heart disease, and n = 30 heart disease and hyperthyroidism). ELISA-based measurements were described as thyroid hormones, IL-6 and proBNP. Glucose, lipid profile, and renal functioning were characterized as Cobas c111 chemistry tests. Descriptive statistics, one-way ANOVA, Pearson correlation, Welch t test, and ROC analysis were performed. Results: There was no significant difference in age among groups (p = 0.159). FT4, FT3, TSH, IL-6, proBNP, BMI, triglycerides, glucose, creatinine and urea were found to have strong group effects (all p < .001). The highest level of IL-6 and proBNP was observed in the heart disease with hyperthyroidism. The largest differences were observed in the proBNP (116.00 vs. 847.22 pg/mL, p <.001, d = 4.29) and IL-6 (4.07 vs. 7.62 pg/mL, p <.001, d = 2.41) in the direct comparison between hyperthyroidism with carbimazole proBNP correlated positively with IL-6 (r = .70, p < .001). TSH correlated inversely with FT4 (r = -.79, p < .001). ProBNP had an AUC of 1.000 and IL-6 had an AUC of 0.961 to discriminate heart disease among hyperthyroid patients. Conclusion: Heart disease patients who had hyperthyroidism had a different profile that was characterized by increased cardiac stress, increased inflammatory load, and poor metabolic and renal indices. ProBNP and IL-6 were the best predictors of cardiac involvement in this cohort.